SELECTING CRITERIAS OF PATIENTS FOR DENTAL IMPLANTS - Cencanșciuc Cristina; Florea Adelina; Cretu Cosmin; Tibeica Andreea; Curca Razvan; Tibeica Silviu Catalin; Agop-Forna Doriana; Norina Forna (Romanian Dental Association for Education, 2023)
Aim of the study: In order to achieve an adequate dental medical treatment based on the use of dental implants and to prevent treatment failure, it is advisable for the dentist to know as many details as possible about the patient. In order to achieve this, the doctor must know the general and local diseases, to establish some criteria that will decide whether medical treatment based on dental implants can be performed or not. The purpose of this study is to describe what are the criterias that the dentist must follow in order to determine which are the future suitable candidates for dental implant treatment. Materials and methods: To write this article, the authors analyzed and compared several specialized medical research studies in this field. They analyzed several articles from several years of study to get an overview of the criterias needed to select patient candidates for dental implants. Results and Conclusions: The dentist's decision to perform a treatment focused on the use of dental implants is made based on a combination of factors. It is important to have a proper history of the patient and to know all general and local factors that might lead to a future failure. Lack of communication and knowledge of the patient by the doctor or only partial knowledge of risk factors will lead to a failure of medical treatment.